Novas perspectivas de políticas na área da atividade física e envelhecimento - Costa, José Luiz Riani [UNESP] (My University, 2007)
The world elderly population has increased and, as a consequence, problems associated with the aging process assume greater relevance. In Brazil, this process is occurring quickly, which makes it difficult to regulate social and health systems to meet the new demands. The rapid populational aging is remarkable for its effects on health, including risk factors for non-transmissible diseases, which are the most prevalent causes of mortality. Physical activity, when performed on a regular basis and well planned, contributes to reduce the suffering of older individuals. In addition, physical activity requires psychosocial involvement, increases self-esteem and engages the cognitive functions. Another benefit of physical activity is its effect on the prevention and rehabilitation of health problems in the elderly, as well as for both overall functional fitness and specific fitness components (flexibility; coordination; agility and balance; strength; and aerobic capacity). Therefore, municipal authorities should promote physical activity programs and exercise sessions could be added to the programs of groups for the elderly.
New perspectives of policy in the area of the physical activity and aging
Keywords: Health; Older people; Physical activity; Quality of life